Increasing the Economic Value of Mangrove Plants Through Ecoprint Product Manufacturing Training: Peningkatan Nilai Ekonomi Tanaman Mangrove Melalui Pelatihan Pembuatan Produk Ecoprint - Emi Roslinda; Lestariningsih, Siti Puji; Astiani, Dwi; Ekyastuti, Wiwik; Ekamawanti, Hanna Artuti (Universitas Lancang Kuning, 2024)
Setapuk Besar Sub-district has a mangrove area due to community conservation independently. However, few people use mangrove plant leaves as natural dyes and essential ingredients for eco-print products. This service activity is intended so the community can independently produce high-quality, attractive eco-print products. The methods applied are a presentation of material, discussion, demonstration, and practice of making eco-print products using the pounding technique. This PKM activity has increased their knowledge and skills regarding using mangrove plant leaves as natural dyes to manufacture eco-print products. The participants' enthusiasm, consisting of Surya Perdana Mandiri NGO members and Setapuk Besar Sub-District PKK women, understood the training material and practiced it at each activity stage. Based on the results of the questionnaire as an evaluation material for PKM activities, it is known that there has been a very significant change in knowledge and skills (above 80%) of the training participants for making eco-print products to increase the economic value of mangrove plants.